If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + t = -3 Solving -16 + t = -3 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + t = -3 + 16 Combine like terms: -16 + 16 = 0 0 + t = -3 + 16 t = -3 + 16 Combine like terms: -3 + 16 = 13 t = 13 Simplifying t = 13
| 24-3d=3d | | 5-3.58= | | 8d-5+7d-9b= | | 5d+9-4d=51+5d | | 5-35/8= | | -3.6-6z-6.9-3z=-8z-8.7 | | -0.4a=-2 | | (150-2X)(100-2X)=10400 | | 2n-23=-6n-3(6n-1) | | 2-7(d-1)=3(d-2)-5(d-3) | | (150-2X)(100-2X)=0 | | 3x-6=20+4x | | 1.75p=9.25 | | -26-2b=-7(b+3) | | -[9x-(2x+4)]=-5-[4(3x-3)-3x] | | -15n=-5 | | -0.7=9.1 | | 16=d-12 | | x-2.25=-3 | | -5(-6k-1)=8k-39 | | 6x-2y+7=180 | | 40p+32=8p-192 | | 6x-12=10x-14 | | 24x-2x^2-6=0 | | x^2+x-4294967295=0 | | 8+2=2+5 | | 4a+19=2a-15 | | 24x-2x^2=6 | | x/3-10=-6 | | 6x-2y=172 | | 4za+19=2a-15 | | -7x-6=-4x-5x |